Developing a character-education-based interactive video for enhancing students’ conceptual understanding in Biology - Nurin Afrina; Miza Nina Adlini (Inovasi Kurikulum, 2025)
Students’ low conceptual understanding of Biology learning is often attributed to the dominance of conventional methods that are monotonous and less engaging, resulting in low motivation. This study aimed to develop a character-education-based interactive video on the human digestive system for eleventh-grade high school students using Canva. The research employed a Research and Development (RnD) approach with the ADDIE model, comprising Analyze, Design, Develop, Implement, and Evaluate stages. The product was tested on 30 students from a Madrasah Aliyah Negeri (MAN) in Medan. Instruments included expert validation sheets for content and media, teacher and student response questionnaires, and conceptual understanding tests. Data were analyzed using descriptive quantitative methods through validity, practicality, and effectiveness tests with the N-Gain calculation. The results indicated that the developed media was highly valid based on expert assessment, highly practical according to teacher and student responses, and effective in improving conceptual understanding with a high N-Gain category. The implication of this study is that character-education-based interactive video has the potential to be applied in Biology learning to reinforce positive character values among students.   Abstrak Rendahnya pemahaman konsep peserta didik dalam pembelajaran Biologi sering disebabkan oleh penggunaan metode konvensional yang monoton dan kurang bervariasi sehingga membuat peserta didik kurang termotivasi. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa video interaktif berbasis pendidikan karakter pada materi Sistem Pencernaan manusia untuk peserta didik kelas XI SMA dengan memanfaatkan aplikasi Canva. Penelitian menggunakan pendekatan Research and Development (RnD) dengan model ADDIE yang mencakup tahap Analyze, Design, Develop, Implement, dan Evaluate. Uji coba dilakukan pada 30 peserta didik di salah satu Madrasah Aliyah Negeri (MAN) di Medan. Instrumen penelitian meliputi lembar validasi ahli materi dan media, angket respons guru dan peserta didik, serta tes pemahaman konsep. Data dianalisis secara deskriptif kuantitatif melalui uji kevalidan, kepraktisan, dan efektivitas menggunakan N-Gain. Hasil penelitian menunjukkan bahwa media yang dikembangkan sangat valid berdasarkan penilaian ahli, sangat praktis berdasarkan respons guru dan peserta didik, serta efektif meningkatkan pemahaman konsep dengan kategori N-Gain tinggi. Implikasi dari penelitian ini adalah video interaktif berbasis pendidikan karakter berpotensi digunakan dalam pembelajaran Biologi untuk mendukung penguatan nilai-nilai karakter positif pada peserta didik. Kata Kunci: Canva; media pembelajaran; pendidikan karakter; sistem pencernaan; video interaktif